A large-size TC4 titanium alloy bar for a large aircraft engine fan integral blade disk and its preparation method

By using large TC4 titanium alloy ingots and multiple upsetting and recrystallization processes, large-sized TC4 titanium alloy rods with diameters of Φ400~800mm were prepared, which solved the problem of difficulty in preparing large-sized TC4 titanium alloy rods in the prior art, and achieved high strength, high plasticity and tissue uniformity bar preparation, meeting the needs of the overall blade disc of large aero engine fans.

CN119259734BActive Publication Date: 2025-05-02BAOSHAN IRON & STEEL CO LTD +2
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411783663.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-05-02
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The prior art is difficult to prepare large-size TC4 titanium alloy rods that meet the overall blade requirements of large aero engine fans, and the hot processing window of titanium alloy is narrow, resulting in difficult to ensure the deformation effect and the uniformity of internal temperature distribution.

Method used

A large TC4 titanium alloy ingot with a diameter of Φ860~1000mm was used to prepare the blank after at least three vacuum consumable smelting, and the blank was prepared by 2 to 3 fire upsettings, and alternately upsettings and cooling in the β-phase zone and the two-phase zone. The deformation amount per fire was controlled to be 40~95%. The grains were refined through multiple recrystallization and adjustment of the structure, and finally a large-scale TC4 titanium alloy rod with isometric structure was obtained.

Benefits of technology

The prepared TC4 titanium alloy rod has a diameter of Φ400~800mm, a primary α phase content of up to 70~90%, a grain size of ≤20μm, an unequal axis KD≤1.5, and has high tensile strength, yield strength, elongation and fracture toughness, meeting the preparation requirements of the overall blade disc of large aircraft engine fans.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259734B_ABST
    Figure CN119259734B_ABST
Patent Text Reader

Abstract

The invention discloses a large-size TC4 titanium alloy bar for a large-scale aircraft engine fan integral blade disk and a preparation method thereof. A large-size TC4 titanium alloy ingot with a diameter of Φ860-1000 mm is used, and a blank is formed by 2-3 times of upsetting and drawing, and the deformation amount of each time is controlled to be 40-70% for full deformation; then, the blank is upset and drawn for 3-7 times, and the deformation amount of each time is controlled to be 40-95%, and the upsetting temperature is controlled to be carried out in a β phase region and a two-phase region, and the cooling mode after upsetting is changed, so that the organization morphology is finally transformed into an equiaxed organization, and the primary α phase content in the organization is increased, and the primary α phase content is as high as 70-90%, so as to obtain a large-size TC4 titanium alloy bar with good strength and plasticity, and the diameter of the bar is Φ400-800 mm, which can be directly used for the production of the integral blade disk, thereby further broadening the processing and application potential of titanium alloys and enriching the application field of titanium alloys.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium alloy hot processing, and in particular relates to a large-size TC4 titanium alloy bar for a large-scale aircraft engine fan integral blade disk and a preparation method thereof. Background Art

[0002] Titanium alloys have the characteristics of high specific strength and excellent high / low temperature resistance. They are the preferred materials for important components such as aircraft engine fans, compressor disks and blades. The processing of aircraft engine integral blades mostly adopts linear friction welding technology, but this technology is prone to defects in the welds, especially the lack of fusion at the edges and corners of the welds, which may cause joint fractures and lead to flight accidents. In order to improve the welding quality, the isothermal upsetting process can achieve uniform and controllable changes in the material microstructure, thereby obtaining a more dense, uniform and stable integral blade.

[0003] With the rapid development of aviation, aircraft specifications have gradually increased, and with it comes higher requirements for engine size and processing blanks in terms of size, uniformity of structure, etc. Compared with materials such as steel, titanium alloys have low thermal conductivity and poor temperature sensitivity, resulting in a narrow thermal processing window. This makes the processing of large-sized TC4 titanium alloy bars more difficult, especially when the size increases, the deformation effect of the bars and the uniformity of the internal temperature distribution are difficult to guarantee, which directly affects their organizational transformation and mechanical properties.

[0004] Chinese patent publication number CN116765121A discloses "a method for preparing TC4 bars, its application and production system", which includes heating, rough rolling, intermediate rolling and finishing rolling in sequence, and a temperature supplement is performed before rough rolling to make up for the temperature difference during rough rolling, and a secondary temperature supplement is performed between finishing rolling and final rolling to make up for the temperature difference caused by rough rolling and finishing rolling. Thus, the uniformity of the structure and appearance of the obtained TC4 bars is improved.

[0005] Chinese patent publication number CN116673422A discloses "TC4 titanium alloy large-size forged bar upsetting and drawing method", which is carried out by upsetting and drawing 2 to 3 times in each fire. In each fire, the predetermined amount is first upset and then drawn to a predetermined aspect ratio, and the deformation amounts of upsetting and drawing are different. This provides a method for effectively combining deformation gradient distribution and cross-fire drawing, reduces the degree of cracking of the billet during the thermal deformation process of each fire, improves the uniformity of the bar structure, and improves the yield rate of TC4 forged bars. The obtained bars have a diameter of Φ200~300mm and a length of 1800~2000mm.

[0006] Chinese patent publication number CN118600279A discloses a method for preparing large-size bars of TC11 high-temperature titanium alloy, which is mainly to solve the instability of mechanical properties of titanium alloy bars finally prepared by traditional methods. Although it mentions that large-size TC11 high-temperature titanium alloy bars can be prepared, the specific size that can be prepared is not specified, and the patent involves TC11 titanium alloy, not TC4 titanium alloy.

[0007] Chinese patent publication number CN116727583A discloses a method for preparing large-size titanium alloy bars, which uses water cooling to increase the nucleation rate of the billet, increase the number and uniform distribution of nuclei of the material, and improve the overall uniformity of the material's organization and performance. However, its maximum specification can only be Φ450mm in diameter.

[0008] Chinese patent publication number CN114888219A discloses a method for preparing large-size bars of Ti6Al4V titanium alloy. By designing the corresponding deformation amount after heating in different phase regions, the billeting stage is subjected to large deformation upsetting in the β single-phase region to fully break the cast grains and refine the grain size; finally, in the forming stage, small deformation upsetting is performed in the α+β two-phase region. Through multiple small deformations, the stability of the process and further refinement of the grains are ensured. This method optimizes the hot working process and flow, reduces the number of upsetting fires, improves the uniformity of the bar structure and the consistency of performance, and obtains a bar diameter of Φ200~450mm. The diameter of the bar obtained by this patent is relatively small.

[0009] Chinese patent publication number CN111889597A discloses a method for upsetting large-sized bars of TC4 titanium alloy. By strictly and effectively controlling the upsetting temperature, upsetting frequency, upsetting speed and deformation amount of each pass, it is not only beneficial to control the temperature of the bar, but also to make the internal and external temperature uniformity of the upset bar higher, and prevent the bar temperature from exceeding the transformation temperature of the β phase of the TC4 titanium alloy during the upsetting process, thereby ensuring the uniformity of the structure of the bar. The large-sized TC4 titanium alloy bar has no complete original β grain boundary, and is composed of equiaxed α+grain boundary β. The initial α content is about 50%, and the obtained bar diameter is Φ200~450mm. The bar diameter obtained by this patent is smaller.

[0010] Chinese patent publication number CN111286686A discloses a short-process preparation method for large-size bars of fine equiaxed structure of TC4 titanium alloy. The patent effectively breaks the primary strip-shaped α phase in the TC4 titanium alloy ingot through near-β forging and rapid cooling after forging, converting it into fine equiaxed α balls and forming fine-grained structure, solving the problem of excessive growth of primary α phase caused by too slow air cooling rate after forging of large-size billets, and introducing a large number of vacancies to provide energy for static recrystallization during the heating and insulation process of subsequent fires, significantly improving the grain refinement efficiency of a single fire, and obtaining an intermediate forging billet composed of fine equiaxed structure, needle-shaped secondary α phase and β matrix. The cross-sectional diameter of the obtained TC4 titanium alloy bar is 200mm~300mm, the length is 5000mm~8000mm, and the primary equiaxed α phase grain size rating is not lower than the 8-level requirement of the GB / T 6394-2017 metal average grain size determination method. The bar obtained by this patent also has a lower grain size and a smaller diameter.

[0011] Chinese patent publication number CN108097852A discloses a method for upsetting and drawing large-size bars of TC4 titanium alloy. The patent adopts one upsetting and one drawing operation to replace the original three upsetting and three drawing operations, which simplifies the operation, reduces production costs and material losses, increases the degree of material deformation, and can more fully crush the core structure to achieve equiaxed. Moreover, as the operation proceeds, the temperature of the forging billet gradually decreases, which is conducive to the crushing of grains and the transformation of organizational morphology, and improves the organizational uniformity of large-size TC4 alloy bars. The diameter of the obtained bar is Φ120mm.

[0012] Chinese patent publication number CN114457259A discloses a fine-grained TC4 titanium alloy rod and a preparation method thereof. By adding trace amounts of P and S elements to the existing TC4 titanium alloy and controlling the mass ratio of the two to be (1~4):(1~10), the P and S elements are used to weaken the grain boundary bonding force of the titanium alloy, which brings convenience to the subsequent preparation of the upsetting and drawing process. The main purpose is to fully deform and refine the β grains. It is suitable for the industrial production of fine-grained TC4 titanium alloy ingots with specifications of Φ280mm~Φ920mm, but the diameter of the obtained rod is only Φ300mm.

[0013] In summary, the specifications of the currently available TC4 titanium alloy bars are relatively small and cannot meet the needs of large aircraft engine manufacturing. Therefore, it is necessary to prepare a large-size TC4 titanium alloy bar for large aircraft engine fan integral blades to meet the needs of future large-size aircraft engine manufacturing. Summary of the invention

[0014] The purpose of the present invention is to provide a large-size TC4 titanium alloy bar for a large aircraft engine fan integral blade disk and a preparation method thereof. The diameter of the obtained TC4 titanium alloy bar is Φ400~800mm, the primary α phase content in the microstructure of the TC4 titanium alloy bar is as high as 70%~90%, the structure is equiaxed and evenly distributed, the grain size is ≤20μm, and the anisotropy K D ≤1.5, tensile strength of the bar ≥950MPa, yield strength ≥900MPa, elongation ≥13%, cross-sectional shrinkage ≥38%, Brinell hardness HB (indentation diameter) ≥3.36mm, fracture toughness ≥65MPa·m 1\2 ; The tensile strength of TC4 titanium alloy rods at 400℃ is ≥630MPa, the elongation is ≥18%, and the cross-sectional shrinkage is ≥45%, which meets the preparation requirements of large aircraft engine fan integral blades.

[0015] To achieve the above purpose, the technical solution of the present invention is as follows:

[0016] A method for preparing a large-size TC4 titanium alloy bar for a large-scale aircraft engine fan integral blade disk comprises the following steps:

[0017] S1: Preparation of titanium alloy ingot

[0018] The diameter of TC4 titanium alloy ingot is Φ860~1000mm;

[0019] S2: Preparing the blank

[0020] The TC4 titanium alloy ingot obtained in step S1 is subjected to 2-3 times of upsetting to obtain a blank; the deformation amount of each time is 40-70% and the upsetting temperature is 1020-1200°C;

[0021] S3: Rod preparation

[0022] The billet is subjected to 3 to 7 times of upsetting and drawing to obtain a bar with a diameter of Φ400 to 800 mm. The deformation amount of each upsetting and drawing is 40 to 95%. During the upsetting and drawing process, the heating and insulation temperature of the billet is alternately carried out in the β phase region and the two-phase region. The temperature in the β phase region is 1020 to 1080°C, and the temperature in the two-phase region is 950 to 980°C. After upsetting and drawing in the β phase region, water cooling is carried out, and after upsetting and drawing in the two-phase region, water cooling or air cooling is carried out.

[0023] Preferably, in step S1, the titanium alloy ingot is obtained by at least three vacuum consumable smelting processes.

[0024] Preferably, in step S2, the TC4 titanium alloy ingot is subjected to two upsetting and drawing processes to obtain a blank, and the specific operation is as follows: the TC4 titanium alloy ingot is kept at 700-900°C for 1-5h, then heated to 1100-1180°C and kept for 5-8h, and then upsetting and drawing to Φ700-900mm to obtain an octagonal blank; thereafter, the ingot is kept at 1020-1080°C for 1-3h, and after keeping the temperature, the ingot is upset and drawn to Φ400-800mm to obtain a blank, which is then water-cooled.

[0025] Preferably, in step S3, the blank is heated and kept warm in the β phase region or the two-phase region before each upsetting;

[0026] If the heating and holding temperature before the first upsetting is in the β phase region, then the first upsetting is carried out; if the heating and holding temperature before the second upsetting is in the two-phase region, then the second upsetting is carried out, and after the second upsetting, the temperature is held in the β phase region;

[0027] If the heating and insulation temperature before the first fire upsetting is in the two-phase region, then the first fire upsetting is carried out; if the heating and insulation temperature before the second fire upsetting is in the β phase region, then the second fire upsetting is carried out; if the heating and insulation temperature before the third fire upsetting is in the two-phase region, then the third fire upsetting is carried out, and insulation is carried out in the β phase region after the third fire upsetting.

[0028] Preferably, in step S3, the blank is subjected to 5 times of upsetting to obtain a bar with a diameter of Φ400-800 mm, and the specific operation is as follows:

[0029] S31: Put the blank into the furnace at a furnace temperature of 700-900°C, and after a heating time of ≥2.5h, the temperature reaches 1020-1080°C, and is kept at this temperature for 3-6h, and then is upset and drawn to Φ400-800mm, and then water-cooled to obtain the first bar blank;

[0030] S32: the first bar blank is kept at 950-980°C for 2-8 hours, and the first bar blank is upset and drawn to Φ400-800mm after being kept; it is upset and drawn to Φ400-800mm again; it is then kept at 1020-1080°C for 5-7 hours and then water-cooled to obtain a second bar blank;

[0031] The second S33 bar blank is kept at 950-980°C for 4-6 hours, and the second bar blank after being kept is upset and drawn to Φ400-800mm, and then water-cooled or air-cooled to obtain the third bar blank;

[0032] The third S34 bar blank is kept at 1020-1080°C for 5-7h, and the third bar blank after being kept is upset to Φ400-800mm, and then water-cooled to obtain the fourth bar blank;

[0033] The fourth S35 bar blank is kept at 950-980°C for 1-3h, and after being kept warm, the fourth bar blank is upset and drawn to Φ400-800mm, and then water-cooled or air-cooled, and finally a large-sized bar with a diameter of Φ400-800mm is obtained.

[0034] Preferably, the cooling time of water cooling or air cooling is ≥ 1 h.

[0035] A large-size TC4 titanium alloy bar for a large-scale aircraft engine fan integral blade disk prepared by the method of the present invention, wherein the components of the TC4 titanium alloy bar include, by weight percentage: Al: 5.50-6.75%, V: 3.5-4.5%, Fe≤0.3%, Si≤0.15%, C≤0.05%, B≤0.0014%, Y≤0.005%, N≤0.05%, H≤0.0125%, O≤0.20%, and the balance is Ti and unavoidable impurities, a single impurity is ≤0.1%, and the total amount of impurities is ≤0.2%;

[0036] The microstructure of the TC4 titanium alloy bar is a uniformly distributed equiaxed structure, with a grain size of ≤20 μm and an unequal axiality K D ≤1.5, the primary α phase content is 70~90%, and the primary α phase grain size rating reaches 10~12 grades in GB / T6394-2017 metal average grain size determination method;

[0037] The diameter of the TC4 titanium alloy rod is Φ400-800 mm.

[0038] The TC4 titanium alloy bar of the present invention has a tensile strength of ≥950MPa, a yield strength of ≥900MPa, an elongation of ≥13%, a cross-sectional shrinkage of ≥38%, a Brinell hardness HB (indentation diameter) of ≥3.36mm, and a fracture toughness of ≥65MPa·m 1\2 ; At 400℃, the tensile strength of TC4 titanium alloy rod is ≥630MPa, the elongation is ≥18%, and the cross-sectional shrinkage is ≥45%.

[0039] In the manufacturing method of the present invention:

[0040] The present invention uses TC4 titanium alloy ingots with a diameter of Φ860~1000mm, which are obtained through at least three vacuum self-consumption processes. Large ingots are selected to meet the requirements of upsetting large-sized bars, while the ingots selected for the preparation of conventional small-sized bars are also smaller. The smaller-sized ingots have better forgeability during the upsetting process and are easier to forge. The present invention uses large ingots for upsetting. In order to obtain a better upsetting effect, the difficulty of upsetting is correspondingly increased.

[0041] The present invention uses 2-3 fire upsetting to make a blank, controls the upsetting temperature at 1020-1200°C in the beta phase region, controls the deformation amount of each fire at 40-70%, breaks the cast structure of the ingot, makes the grains fine, adjusts the structure morphology, and provides an easily broken structure (basket structure, martensite structure, etc.) for subsequent upsetting; at the same time, upsetting at the beta phase temperature reduces surface cracking during the upsetting process and improves the yield rate; after cooling, the blank is sawn and divided, provides a suitable height-to-diameter ratio for subsequent upsetting, and improves the effect of subsequent upsetting structure breaking.

[0042] Preferably, in the process of upsetting and drawing the blank, the TC4 titanium alloy ingot is kept at 700-900° C. for 1-5 hours, then heated to 1100-1180° C. for 5-8 hours, and then upset and drawn to Φ700-900 mm to obtain an octagonal blank;

[0043] (1) Gradually heating to the blanking temperature: Since the thermal conductivity of titanium alloy is relatively small, the large ingot with a larger diameter (thickness) used in the present invention needs to be preheated at a low temperature to prevent cracking inside the blank; then gradually heating up helps to control the structural changes during the heating process and avoid excessive heating that leads to a decrease in material performance; gradually heating up can reduce the thermal stress caused by the temperature gradient, thereby reducing the risk of cracks in the material during the upsetting process;

[0044] (2) Structural changes: The large ingot obtained after smelting is a classic Widmanstatten structure, that is, the coarse original β grains are clear and complete in the microstructure, there is a continuous α phase on the grain boundary, and a larger "bundle" is formed in the original β grain. In the same "bundle", there are more α phases parallel to each other and in the same orientation; coarse lamellar α phases in the grains and β phases between the lamellar phases, this structure usually leads to reduced plasticity and toughness of the material and increased brittleness; in the present invention, after upsetting at 1100-1180°C in the β phase region, the β grains are elongated and flattened along the direction of metal flow, and then nucleation and recrystallization are first developed on the original β grain boundary, so that the β grains are refined; when the new β grains recrystallized on the original β grain boundary grow and contact each other, the finest grain size of the β grains is obtained;

[0045] (3) Heat to 1100-1180℃ and keep warm for 5-8h: This is the ingot opening temperature. Keep warm to ensure uniform temperature of the entire ingot, avoiding uneven processing and internal stress caused by uneven temperature. By keeping warm, the thermal stress generated by rapid heating inside the material can be reduced, reducing the risk of cracking.

[0046] (4) The intermediate billet obtained is an octagonal billet: Compared with circular or square cross-sections, the corners of the octagonal cross-section can better guide the metal flow, making the metal more evenly distributed during the upsetting process and reducing the stress concentration at the corners and edges. Through octagonal upsetting, the deformation of the material in the β phase region can be increased, thereby improving the uniformity of the material's structure and mechanical properties. Octagonal upsetting can reduce defects such as cracks and folds during the upsetting process, because the octagon can more evenly distribute the upsetting force and reduce local stress concentration; compared with circular or square cross-sections, the octagonal cross-section has more edges and corners, which can improve heat conduction and make the material temperature more uniform during the heating process.

[0047] The obtained octagonal billet is kept at 1020-1080°C for 1-3h, and then upset and drawn to Φ400-800mm to obtain the billet, which is then water-cooled or air-cooled.

[0048] (1) Structural changes during upsetting: The Widmanstätten structure has strong heredity, but this heredity can be weakened through the thermoplastic deformation during the first upsetting process, making the impurity crushing in the ingot more diffusely distributed. The residual β structure is further crushed, and broken β grains are obtained at this time. When the alloy ends deformation above the β transformation temperature, during the air cooling process, when the temperature drops to the β phase transformation temperature, a β→α transformation occurs, and a lamellar α phase first precipitates along the boundary of the original β grain, and then a lamellar α phase precipitates along the grain. After this step, finer β grains, thinner grain boundary α and α lamellar structure within the grain are obtained;

[0049] (2) Reasons for upsetting before drawing: During upsetting and drawing, upsetting first (upsetting and drawing) can give a larger deformation, remove defects, refine impurities, and store energy to provide energy for recrystallization during drawing. When a large deformation is required in the high temperature zone, upsetting first can improve forgeability, make the metal flow more uniform, and reduce the need for frequent trimming;

[0050] Improved uniformity of structure: Upsetting first can increase the deformation of the β phase region, which helps to improve the uniformity of the structure of the entire bar, especially between different parts of the bar (such as the edge, 1 / 2R and the core). This is crucial to ensure the consistency of the performance of the bar. Upsetting first and then stretching helps to optimize the metal flow, making the material flow more uniform during the stretching process and reducing defects caused by uneven local deformation;

[0051] (3) The deformation of each upsetting and drawing process is controlled between 40% and 95% in order to refine the grains, improve the microstructure, reduce upsetting and drawing defects, and improve forgeability. A larger deformation can increase energy storage and help promote the recrystallization of the material, such as α→β transformation, thereby affecting the microstructure and macroscopic properties of the material, reducing the anisotropy of the material, and ensuring the core performance, thereby improving the overall performance and production efficiency of the titanium alloy bar.

[0052] The obtained billet is subjected to 3 to 7 times of upsetting to obtain a large-size TC4 titanium alloy bar with a diameter of Φ400~800mm. During the upsetting process, the upsetting is controlled in two upsetting temperature zones, the β phase zone and the two-phase zone, and the deformation of each fire is controlled at 40~95%. Combined with sufficient upsetting and changes in cooling methods (water cooling is used after upsetting in the β phase zone, because accelerating the cooling rate will be conducive to recrystallization to obtain finer β grains, thinner grain boundary α and α sheet structure in the crystal, which is beneficial to further refine the structure, so water cooling is used. Two-phase After zone upsetting and drawing, water cooling or air cooling is used. On the one hand, residual stress is reduced to prevent deformation; on the other hand, it is conducive to further refinement of lamellar or equiaxed structures with high internal energy, that is, sub-dynamic recrystallization and subsequent static recrystallization occur. Through multiple recrystallizations, the grains are further refined, and at the same time, the organizational morphology is continuously adjusted to gradually transform from basketweave structure and martensite structure to basketweave structure and partial equiaxed structure, and then further to equiaxed structure and partial basketweave structure, and finally a completely evenly distributed equiaxed structure is obtained, with a grain size of ≤20μm and anisotropy K D ≤1.5, and increase the content of primary α phase, the content of primary α phase is as high as 70~90%, and the grain size rating reaches 10~12 grades in the GB / T6394-2017 metal average grain size determination method, so that the obtained TC4 titanium alloy rod with larger diameter has better strength and plasticity.

[0053] Preferably, the blank is subjected to 5-time upsetting to obtain a rod with a diameter of Φ400-800 mm.

[0054] S31: Put the bar blank into the furnace at a furnace temperature of 700-900°C, and after a heating time of ≥2.5h, the temperature reaches 1020-1080°C, and is kept at this temperature for 3-6h, and then is upset and drawn to Φ400-800mm to obtain the first bar blank;

[0055] Organizational changes: β grains are further broken, and the organization is fully broken through upsetting, with small and uniform grains; grains are recrystallized and refined in the β phase region, and the organizational morphology is adjusted to a basketweave organization and a partially equiaxed organization.

[0056] S32: the first bar blank is kept at 950-980°C for 2-8h, and the first bar blank is upset and drawn to Φ400-800mm after being kept, and the first bar blank is upset and drawn to Φ400-800mm again; then, the first bar blank is kept at 1020-1080°C for 5-7h and water-cooled to obtain a second bar blank;

[0057] The organization is fully broken by upsetting, and the grains are small and uniform; heating in the two-phase region, the grains are recrystallized and the grains are refined, and the organization morphology is adjusted to a basket organization and a partially equiaxed organization. The grain boundary α phase and the lamellar α phase are flattened and elongated and broken along the metal flow direction, and the difference between the grain boundary and the α phase in the grain gradually disappears. After 40-95% deformation, there is no sign of lamellar organization. At the deformation degree in the two-phase region, the alloy is fully recrystallized, and the recrystallization of the α phase is faster than that of the β phase, which promotes the formation of the primary α phase. The grains after recrystallization are spherical, which are called primary equiaxed α grains. At this time, the organization is an equiaxed primary α phase and a lamellar β transformation organization composed of (α+β) phases.

[0058] Cooling after plastic deformation in the β zone is very important, because accelerating the cooling rate will be conducive to recrystallization to obtain finer β grains, thinner grain boundary α and α sheet structure within the grain, which is beneficial to further refine the structure. Therefore, water cooling is used after insulation.

[0059] The second S33 bar blank is kept at 950-980°C for 4-6 hours, and the second bar blank after being kept is upset and drawn to Φ400-800mm, and then water-cooled or air-cooled to obtain the third bar blank;

[0060] The structure is fully broken by upsetting and the grains are small and uniform; heating in the two-phase region causes the grains to be recrystallized and refined, and the structure morphology is adjusted to a basketweave structure and a partially equiaxed structure.

[0061] The third S34 bar blank is kept at 1020-1080°C for 5-7 hours, and the third bar blank after being kept is upset to Φ400-800mm, and then water-cooled to obtain the fourth bar blank;

[0062] The β grains are further broken, and the organization is fully broken through upsetting, and the grains are fine and uniform; in the β phase region, the grains are recrystallized and the grains are refined, and the organization morphology is adjusted to a basketweave organization and a partially equiaxed organization.

[0063] The fourth S35 bar blank is kept at 950-980°C for 1-3h, and after being kept warm, the fourth bar blank is upset and drawn to Φ400-800mm, and then water-cooled or air-cooled to finally obtain a large-sized bar with a diameter of Φ400-800mm.

[0064] The structure is fully broken by upsetting and drawing, and the grains are small and uniform; the grain boundaries are fully broken by heating in the two-phase region, and the final structure morphology is a completely equiaxed structure.

[0065] Compared with the prior art, the present invention has the following beneficial effects:

[0066] 1. The present invention is directed to large-sized TC4 titanium alloy bars for large aircraft engine fan integral blade disks.

[0067] In the past, the TC4 titanium alloy bars used for some aircraft engine fan blades were approximately less than Φ400mm (most of them were less than Φ300mm bars), the weight of the bars used for a single blade disk was also relatively light, and the ingots selected for the bars were also less than Φ860mm. As the bar specifications became smaller, the ingot specifications also became smaller, and the forgeability of the billet during the upsetting process was also better. The upsetting process adopted 2 to 4 fires of upsetting and drawing in the β phase region to open the billet, followed by 4 to 5 fires of upsetting and drawing in the (α+β) two phases and 1 to 2 fires of forming and 4 to 5 fires of upsetting and drawing to obtain bars with performance that meets the requirements.

[0068] The integral blade disk made of rods in the present invention is very large. In the past, TC17 titanium alloy material was used for this type of blade disk. However, due to the low plasticity of TC17 titanium alloy, it is not adaptable in certain usage environments. For this reason, TC4 titanium alloy is selected. The specifications of the rods required are also larger according to the size of the integral blade disk. In order to make the large-sized rods meet the user's technical requirements and each batch has a certain weight, it is necessary to use large ingots to meet the requirements of the upsetting deformation and batch weight of large-sized rods, and optimize the upsetting process of large-sized rods.

[0069] The invention adopts a large TC4 titanium alloy ingot with a diameter of Φ860-1000mm, which is obtained by at least three vacuum self-consumption processes, and then undergoes 2-3 fires of blanking and upsetting combined with sufficient deformation, firstly, the cast structure of the ingot is broken by blanking to make the grains fine, and the structure morphology is adjusted to a basket structure, a martensite structure, etc., so as to provide an easily broken blank structure for subsequent upsetting; then, it undergoes 3-7 fires of upsetting, the deformation amount of each fire is controlled at 40-95%, and the upsetting temperature is controlled to be heated in the β phase region and the two-phase region, and then combined with sufficient upsetting and cooling methods, the ingot is subjected to the first-stage blanking process, and the ingot is subjected to the second ... The changes, through multiple recrystallization, further refine the grains, and continuously adjust the organizational morphology, finally transform the organizational morphology into equiaxed organization, and increase the primary α phase content in the organization, the primary α phase content is as high as 70~90%, so that the large-size TC4 titanium alloy rods have good strength and plasticity, the tensile strength of the rods is ≥950MPa, the yield strength is ≥900MPa, the elongation is ≥13%, the cross-sectional shrinkage is ≥38%, the Brinell hardness HB (indentation diameter d) is ≥3.36mm, and the fracture toughness is ≥65MPa·m 1\2 ; The tensile strength of TC4 titanium alloy bars at 400℃ is ≥630MPa, the elongation is ≥18%, and the section shrinkage is ≥45%;

[0070] 2. The diameter of the large-size TC4 titanium alloy rod prepared by the present invention reaches Φ400~800mm, the composition is a uniformly distributed equiaxed structure, the grain size is ≤20μm, and the anisotropy K D≤1.5, and the content of primary α phase in the organization is increased, the content of primary α phase is as high as 70~90%, and its percentage content far exceeds the bar standard (>40%) used to prepare the integral blade disk of the aircraft engine fan, and the grain size rating reaches 10~12 grades in the GB / T 6394-2017 metal average grain size determination method; thus, a TC4 titanium alloy bar with a larger diameter that can meet the requirements of strength and plasticity is obtained. The TC4 titanium alloy bar can be directly used for the production of integral blade disks, thereby further broadening the processing and application potential of titanium alloys and enriching the application field of titanium alloys. However, most of the existing TC4 titanium alloy bars have a diameter of less than Φ400mm, which cannot meet the production requirements of integral blade disks;

[0071] 3. The present invention uses the large-sized TC4 titanium alloy rods to prepare the integral blade disk, while the existing integral blade disk is mostly made of TC17 titanium alloy materials. However, due to the low plasticity of TC17 titanium alloy, it cannot be used in specific environments. The use of the large-sized TC4 titanium alloy rods of the present invention to prepare the integral blade disk can make the blade disk have high strength and plasticity at the same time, meeting the use requirements of more environments;

[0072] 4. The large-size TC4 titanium alloy rod obtained by the present invention can be directly used in the isothermal upsetting and drawing of the integral blade disk of the aircraft engine fan, thereby further broadening the processing and application potential of titanium alloys and enriching the application field of titanium alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 This is a low-magnification microstructure photograph of the TC4 titanium alloy bar with a diameter of 420 mm in Example 1 of the present invention;

[0074] Figure 2 This is a high-magnification microstructure photograph of the TC4 titanium alloy bar with a diameter of 420 mm in Example 1 of the present invention;

[0075] Figure 3 This is a low-magnification microstructure image of a Φ800 mm large-size TC4 titanium alloy bar obtained in Example 2 of the present invention;

[0076] Figure 4 This is a high-magnification microstructure picture of a Φ800mm large-size TC4 titanium alloy bar obtained in Example 2 of the present invention;

[0077] Figure 5 This is a low-magnification microstructure image of a Φ700 mm large-size TC4 titanium alloy bar obtained in Example 3 of the present invention;

[0078] Figure 6 This is a high-magnification microstructure picture of a Φ700 mm large-size TC4 titanium alloy bar obtained in Example 3 of the present invention;

[0079] Figure 7This is a low-magnification microstructure image of the TC4 titanium alloy bar obtained in the comparative example;

[0080] Figure 8 This is a high-magnification microstructure image of the TC4 titanium alloy rod obtained in the comparative example. DETAILED DESCRIPTION

[0081] The present invention will be further described below in conjunction with the embodiments and drawings.

[0082] Example 1

[0083] The chemical composition ratio of the TC4 titanium alloy rod with a diameter of Φ420 mm is shown in Table 1, and the preparation method thereof comprises the following steps:

[0084] S1 prepares a titanium alloy ingot;

[0085] A Φ860mm titanium alloy ingot was obtained through three vacuum consumable melting processes;

[0086] S2 prepares the blank;

[0087] S21: the alloy ingot in step S1 is kept at 700°C for 1 hour, then heated to 1130°C for 2.5 hours and kept at 1130°C for 5 hours, and an octagonal billet is obtained by upsetting from Φ860 to Φ700mm, and the deformation amount of this fire is 43%;

[0088] The octagonal billet obtained in S22 was kept at 1050℃ for 1h, and then upset and drawn to Φ500mm. The deformation of this fire was 50%, and the billet was obtained, and then water-cooled for 10h;

[0089] S3 rod preparation;

[0090] S31: the blank described in step S22 is put into a heating furnace at a temperature of 850°C, the temperature is raised for 2.5 hours to 1020°C and kept for 3 hours, and then the blank is upset and drawn to Φ500mm. The deformation amount of this fire is 50%, and the first blank is obtained;

[0091] S32 The first bar blank is kept at 950℃ for 2h, and then upset and drawn to Φ500mm, and then upset and drawn to Φ500mm. The deformation of this fire is 60%. Then, it is kept at 1080℃ for 5h and water-cooled for 10h to obtain the second bar blank;

[0092] The second S33 bar blank was kept at 950°C for 4 hours, and was upset and drawn to Φ500mm. The deformation of this fire was 64%, and then water-cooled to obtain the third bar blank.

[0093] The third S34 bar blank was kept at 1020℃ for 5h, and was upset and drawn to Φ420mm. The deformation of this fire was 63%, and then water-cooled to obtain the fourth bar blank.

[0094] The fourth rod blank obtained in S35 is kept at 950℃ for 1h, and is upset and drawn to Φ420mm. The deformation of this fire is 65%. After forging, it is water-cooled for 10h to obtain a Φ420mm diameter TC4 large-size titanium alloy rod.

[0095] The obtained rods were tested for microstructure and mechanical properties, and the properties are shown in Table 2;

[0096] Figure 1 The following is a low-magnification microstructure photograph of a Φ420mm TC4 titanium alloy rod. From the picture, it can be seen that there are no visible cracks, shrinkage holes, pores, folds, inclusions, segregation or other defects that affect use in the microstructure. The low-magnification microstructure has no obvious, visually visible clear grains.

[0097] Figure 2 These are the microstructure photos of the Φ420mm TC4 titanium alloy rods obtained under high magnification. It can be seen from the pictures that the microstructure is equiaxed, the content of primary α phase in the microstructure reaches more than 85%, and the primary α phase grain size rating reaches level 10~12 in the GB / T6394-2017 metal average grain size determination method. Equiaxed primary α phase is distributed on the matrix of β transformation microstructure, all original β grain boundaries are fully broken, and there is no continuous network of α phase on the original β grain boundaries.

[0098] The obtained Φ420mm large-size TC4 titanium alloy bar has a grain size of ≤10μm and an unequal axiality of K D ≤1.5, the isothermal upsetting process can be directly used to prepare the integral blade disk of the aircraft engine fan.

[0099] Example 2

[0100] The chemical composition ratio of the TC4 titanium alloy rod with a diameter of Φ800 mm is shown in Table 1, and the preparation method thereof comprises the following steps:

[0101] S1 prepares a titanium alloy ingot;

[0102] A Φ1000mm titanium alloy ingot was obtained through three vacuum consumable melting processes;

[0103] S2 prepares the blank;

[0104] S21: the alloy ingot in step S1 is kept at 850°C for 4 hours, then heated to 1170°C for 8 hours, and then taken out from the octagonal billet which is upset and drawn from Φ1000mm to 700mm. The deformation of this fire is 70%;

[0105] The octagonal billet obtained in S22 was kept at 1080℃ for 2h, then upset and drawn to Φ600mm, with a deformation of 65% to obtain the billet, which was then water-cooled for 15h;

[0106] S3 rod preparation;

[0107] S31: the bar blank described in step S22 is put into a heating furnace at a temperature of 750°C, the temperature is raised for 3.5 hours to 1070°C and kept for 4 hours, and then the bar blank is upset and drawn to Φ600mm, the deformation amount of this fire is 92%, and then water-cooled to obtain the first bar blank;

[0108] The first bar blank of S32 is kept at 980℃ for 3h, and then upset and drawn to Φ600mm. The deformation of this fire is 85%. Then it is upset and drawn to Φ600mm, kept at 1050℃ for 7h, and then water-cooled for 15h to obtain the second bar blank.

[0109] The second S33 bar blank was kept at 980℃ for 5h, and was upset and drawn to Φ600mm. The deformation of this fire was 83%, and the third bar blank was obtained;

[0110] The third S34 bar blank was kept at 1070℃ for 6h, and was upset and drawn to Φ800mm. The deformation of this fire was 83%, and then water-cooled to obtain the fourth bar blank.

[0111] The fourth S35 bar blank was kept at 980℃ for 2h, and was upset and drawn to Φ800mm. The deformation of this fire was 86%. After forging, it was water-cooled for 15h to obtain a TC4 large-size titanium alloy bar with a diameter of Φ800mm.

[0112] The obtained preform was subjected to macroscopic microstructure and mechanical property tests, and the mechanical properties are shown in Table 2.

[0113] Figure 3 This is a low-magnification organizational picture of the Φ800mm large-size TC4 titanium alloy bar. It can be seen from the picture that there are no visible cracks, shrinkage holes, pores, folds, inclusions, segregation and other defects that affect use. The low-magnification organization has no obvious, visually visible clear grains.

[0114] Figure 4 They are high-magnification organizational pictures of Φ800mm large-size TC4 titanium alloy bars. It can be seen from the pictures that the organization is equiaxed, the content of primary α phase in the organization is more than 80%, and the primary α phase grain size rating reaches 10~12 levels in GB / T 6394-2017 metal average grain size determination method. Equiaxed primary α phase is distributed on the matrix of β transformation organization, all original β grain boundaries are fully broken, and there is no continuous network of α phase on the original β grain boundaries.

[0115] The obtained Φ800mm large-size TC4 titanium alloy bar has a grain size of ≤15μm and an unequal axiality of K D ≤1.5, the isothermal upsetting process can be directly used to prepare the integral blade disk of the aircraft engine fan.

[0116] Example 3

[0117] The chemical composition ratio of the TC4 titanium alloy rod with a diameter of Φ700 mm is shown in Table 1, and the preparation method thereof comprises the following steps:

[0118] S1 prepares a titanium alloy ingot;

[0119] A Φ900mm titanium alloy ingot was obtained through three vacuum consumable melting processes;

[0120] S2 prepares the blank;

[0121] S21: the alloy ingot in step S1 is kept at 880°C for 3 hours, then heated to 1180°C for 3 hours and kept for 6 hours, and an octagonal billet is taken out which is upset and drawn from Φ900mm to 700mm, the deformation of this fire is 59%, and water-cooled after forging;

[0122] The octagonal billet obtained in S22 was kept at 1020℃ for 2h, and then upset and drawn to Φ600mm. The deformation of this fire was 62%, and the billet was obtained, and then water-cooled for 15h;

[0123] S3 rod preparation;

[0124] S31: the blank described in step S22 is then put into a heating furnace at a temperature of 890°C, heated to 1040°C for 3.5h and kept at that temperature for 4h, then the blank is upset and drawn to Φ600mm, the deformation amount of this fire is 85%, and then water-cooled to obtain the first blank;

[0125] The first S32 bar blank was kept at 975℃ for 8h, and then upset and drawn to Φ600mm. The deformation of this fire was 82%. After upsetting and drawing to Φ600mm, it was kept at 1040℃ for 6h and then water-cooled for 15h to obtain the second bar blank.

[0126] The second S33 bar blank was kept at 975℃ for 5h, and then upset and drawn to Φ600mm. The deformation of this fire was 84%, and then air-cooled to obtain the third bar blank.

[0127] The third S34 bar blank was kept at 1040℃ for 6h, and was upset and drawn to Φ700mm. The deformation of this fire was 86%, and then water-cooled to obtain the fourth bar blank.

[0128] The fourth S35 bar blank was kept at 975℃ for 2h, and then upset and drawn to Φ700mm. The deformation of this fire was 80%, and air-cooled for 15h after forging to obtain the fifth bar blank.

[0129] The fifth S36 bar blank was kept at 1040℃ for 7h, upset and stretched to Φ700mm, with a deformation of 78%, and then water-cooled to obtain the sixth bar blank;

[0130] The sixth S37 bar blank was kept at 975°C for 3 hours, and was upset and drawn to Φ700mm. The deformation of this fire was 75%. After forging, it was air-cooled for 13 hours to obtain a TC4 large-size titanium alloy bar with a diameter of Φ700mm.

[0131] The obtained preform was subjected to macroscopic microstructure and mechanical property tests, and the mechanical properties are shown in Table 2.

[0132] Figure 5 This is a low-magnification organizational picture of the Φ700mm large-size TC4 titanium alloy bar. It can be seen from the picture that there are no visible cracks, shrinkage holes, pores, folds, inclusions, segregation and other defects that affect use. The low-magnification organization has no obvious, visually visible clear grains.

[0133] Figure 6 This is a high-magnification organizational picture of a Φ700mm large-size TC4 titanium alloy bar. It can be seen from the picture that the organization is an equiaxed organization, the content of primary α phase in the organization reaches more than 85%, and the primary equiaxed α phase grain size rating reaches 10~12 levels in GB / T 6394-2017 metal average grain size determination method. Equiaxed primary α phase is distributed on the matrix of β transformation organization, all original β grain boundaries are fully broken, and there is no continuous network of α phase on the original β grain boundaries.

[0134] The obtained Φ700mm large-size TC4 titanium alloy bar has a grain size of ≤13μm and an unequal axiality of K D ≤1.5, the isothermal upsetting process can be directly used to prepare the integral blade disk of the aircraft engine fan.

[0135] Comparative Example

[0136] The chemical composition ratio of the TC4 titanium alloy rod with a diameter of Φ400 mm is shown in Table 1, and the preparation method thereof comprises the following steps:

[0137] S1 prepares a titanium alloy ingot;

[0138] A Φ860mm titanium alloy ingot was obtained through three vacuum consumable melting processes;

[0139] S2 prepares the blank;

[0140] S21: the alloy ingot in step S1 is kept at 850°C for 1 hour, then heated to 1150°C for 2.5 hours and kept at this temperature for 5 hours, and an octagonal billet is obtained by upsetting and drawing from Φ860 to Φ700mm, the deformation amount of this fire is 50%, and water cooling is performed after forging;

[0141] The octagonal billet obtained in S22 was kept at 1050℃ for 1h, and then upset and drawn to Φ500mm. The deformation of this fire was 52%, and the billet was obtained, and then water-cooled for 10h;

[0142] S3 rod preparation;

[0143] S31: the blank described in step S22 is put into a heating furnace at 850°C, heated for 2.5h to 1050°C and kept for 3h, then the blank is upset and drawn to Φ500mm, the deformation amount of this fire is 60%, and the first blank is obtained;

[0144] The first rod blank obtained in S32 is kept at 960℃ for 1h, and is upset and drawn to Φ400mm. The deformation of this fire is 62%. After forging, it is air-cooled for 10h to obtain a large-size titanium alloy rod with a diameter of Φ400mmTC4.

[0145] The obtained rods were tested for microstructure and mechanical properties, and the properties are shown in Table 2;

[0146] It can be seen from Table 2 that the diameter of the rods prepared in Examples 1 to 3 of the present invention can reach 400 to 800 mm, the tensile strength of the rods is ≥950 MPa, the yield strength is ≥900 MPa, the elongation is ≥13%, the cross-sectional shrinkage is ≥38%, the Brinell hardness HB is ≥3.36 mm, and the fracture toughness is ≥65 MPa·m 1\2 ; The tensile strength of the TC4 titanium alloy rod at a high temperature of 400°C is ≥630MPa, the elongation is ≥18%, and the cross-sectional shrinkage is ≥45%, indicating that the TC4 titanium alloy rod prepared by the method of the present invention has high strength and high plasticity while having a larger specification, and can meet the preparation requirements of the integral blade disk.

[0147] In the comparative example, only two upsetting and drawing processes were performed during the preparation of the blank, and the cooling method was not clarified after upsetting and drawing. The yield strength of the obtained rod was 820 MPa and the high-temperature tensile strength was 600 MPa, which did not meet the technical requirements of large aircraft engine fan integral blades and could not be used to prepare large aircraft engine fan integral blades.

[0148] Figure 7 The microstructure photograph of the Φ400mm TC4 titanium alloy rod obtained for the comparative example under low magnification is shown. It can be seen from the picture that the low-magnification microstructure is uneven and does not meet the requirements of the Φ220mm rod in GJB1538.

[0149] Figure 8 This is a high-powered microstructure photograph of a Φ400mm TC4 titanium alloy rod obtained for comparison. From the picture, it can be seen that the primary α phase content in the microstructure is about 40%, the primary equiaxed α phase is less, and long strips of α phase are distributed on the matrix of the β transformation microstructure. The original β grain boundary is not fully broken, and there is a small continuous network of α phase on the original β grain boundary. Grain size ≥ 20μm, anisotropy K D ≥10, the macrostructure rating in T direction does not meet the requirements of Φ220mm bars in GJB1538.

[0150] The embodiments described above are only descriptions of the preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

[0151]

[0152]

Claims

1. A method for preparing large-size TC4 titanium alloy bars for large-scale aircraft engine fan integral blade disks, characterized in that: The steps include: S1: Preparation of titanium alloy ingot The diameter of TC4 titanium alloy ingot is Φ860~1000mm; S2: Preparing the blank The TC4 titanium alloy ingot obtained in step S1 is subjected to 2-3 times of upsetting to obtain a blank; the deformation amount of each time is 40-70% and the upsetting temperature is 1020-1200°C; S3: Rod preparation The billet is subjected to 3 to 7 times of upsetting and drawing to obtain a bar with a diameter of Φ400 to 800 mm, with a deformation of 40 to 95% in each upsetting and drawing process. During the upsetting and drawing process, the heating and insulation temperature of the billet is alternately carried out in the β phase region and the two-phase region, with the temperature of the β phase region being 1020 to 1080°C and the temperature of the two-phase region being 950 to 980°C. After upsetting and drawing in the β phase region, water cooling is performed, and after upsetting and drawing in the two-phase region, water cooling or air cooling is performed. The microstructure of the TC4 titanium alloy bar is a uniformly distributed equiaxed structure with a grain size of ≤20μm and an unequal axis K D ≤1.5, the primary α phase content is 70~90%, and the primary α phase grain size rating reaches grade 10~12 in GB / T 6394-2017 metal average grain size determination method; The diameter of the obtained TC4 titanium alloy rod is Φ400~800mm.

2. The method for preparing large-sized TC4 titanium alloy bars for large-scale aircraft engine fan integral blade disks as claimed in claim 1, characterized in that: In step S1, the TC4 titanium alloy ingot is obtained by at least three vacuum consumable smelting processes.

3. The method for preparing large-sized TC4 titanium alloy bars for large-scale aircraft engine fan integral blade disks as claimed in claim 1, characterized in that: In step S2, the TC4 titanium alloy ingot is subjected to two upsetting and drawing processes to obtain a blank. The specific operation is as follows: the TC4 titanium alloy ingot is kept at 700-900°C for 1-5h, then heated to 1100-1180°C for 5-8h, and then upsetting and drawing to Φ700-900mm to obtain an octagonal blank; then, the ingot is kept at 1020-1080°C for 1-3h, and after keeping the temperature, it is upset and drawn to Φ400-800mm to obtain a blank, which is then water-cooled.

4. The method for preparing large-sized TC4 titanium alloy bars for large-scale aircraft engine fan integral blade disks as claimed in claim 1, characterized in that: In step S3, the blank is heated and kept warm in the β phase region or the two-phase region before each upsetting process; If the heating and holding temperature before the first upsetting is in the β phase region, then the first upsetting is carried out; if the heating and holding temperature before the second upsetting is in the two-phase region, then the second upsetting is carried out, and after the second upsetting, the temperature is held in the β phase region; If the heating and insulation temperature before the first fire upsetting is in the two-phase region, then the first fire upsetting is carried out; if the heating and insulation temperature before the second fire upsetting is in the β phase region, then the second fire upsetting is carried out; if the heating and insulation temperature before the third fire upsetting is in the two-phase region, then the third fire upsetting is carried out, and insulation is carried out in the β phase region after the third fire upsetting.

5. The method for preparing large-sized TC4 titanium alloy bars for large-scale aircraft engine fan integral blade disks as claimed in claim 1 or 4, characterized in that: In step S3, the blank is subjected to five times of upsetting to obtain a bar with a diameter of Φ400-800 mm. The specific operation is as follows: S31: Put the billet into the furnace at a temperature of 700-900°C, and after a heating time of ≥2.5h, the temperature reaches 1020-1080°C, and is kept at this temperature for 3-6h, and then it is upset and drawn to Φ400-800mm and water-cooled to obtain the first billet; S32: the first bar blank is kept at 950-980°C for 2-8h, and the first bar blank is upset and drawn to Φ400-800mm after being kept, and the first bar blank is upset and drawn to Φ400-800mm again; then, the first bar blank is kept at 1020-1080°C for 5-7h and water-cooled to obtain a second bar blank; The second S33 bar blank is kept at 950-980°C for 4-6 hours, and the second bar blank after being kept is upset and drawn to Φ400-800mm, and then water-cooled or air-cooled to obtain the third bar blank; The third S34 bar blank is kept at 1020-1080°C for 5-7h, and the third bar blank after being kept is upset to Φ400-800mm, and then water-cooled to obtain the fourth bar blank; The fourth S35 bar blank is kept at 950-980°C for 1-3h, and after being kept warm, the fourth bar blank is upset and drawn to Φ400-800mm, and then water-cooled or air-cooled, and finally a large-sized bar with a diameter of Φ400-800mm is obtained.

6. The method for preparing large-sized TC4 titanium alloy bars for large-scale aircraft engine fan integral blade disks as claimed in claim 1, characterized in that: The cooling time of water cooling or air cooling is ≥1h.

7. The method for preparing large-sized TC4 titanium alloy bars for large-scale aircraft engine fan integral blade disks as claimed in claim 5, characterized in that: The cooling time of water cooling or air cooling is ≥1h.

8. A large-size TC4 titanium alloy bar for a large aircraft engine fan integral blade disk prepared by the method according to any one of claims 1 to 7, characterized in that: The composition of the TC4 titanium alloy rod includes by weight percentage: Al 5.50-6.75%, V 3.5-4.5%, Fe≤0.3%, Si≤0.15%, C≤0.05%, B≤0.0014%, Y≤0.005%, N≤0.05%, H≤0.0125%, O≤0.20%, the balance is Ti and unavoidable impurities, a single impurity ≤0.1%, and a total impurity ≤0.2%; The microstructure of the TC4 titanium alloy bar is a uniformly distributed equiaxed structure, with a grain size of ≤20 μm and an unequal axiality K D ≤1.5, the primary α phase content is 70~90%, and the primary α phase grain size rating reaches grade 10~12 in GB / T 6394-2017 metal average grain size determination method; The diameter of the TC4 titanium alloy rod is Φ400-800 mm.

9. The large-size TC4 titanium alloy bar for a large aircraft engine fan integral blade disk as claimed in claim 8, characterized in that: The TC4 titanium alloy bar has a tensile strength of ≥950MPa, a yield strength of ≥900MPa, an elongation of ≥13%, a cross-sectional shrinkage of ≥38%, a Brinell hardness HB indentation diameter of ≥3.36mm, and a fracture toughness of ≥65MPa·m 1\2 ; At 400℃, the tensile strength of TC4 titanium alloy rod is ≥630MPa, the elongation is ≥18%, and the cross-sectional shrinkage is ≥45%.

Citation Information

Patent Citations

  • Forging method of TC4 titanium alloy large-specification rods

    CN108097852A

  • TC4 titanium alloy fine-equiaxed-structure large-size bar short-process preparation method

    CN111286686A

  • Forging method of TC4 titanium alloy large-specification bar

    CN111889597A

  • TC4 titanium alloy bar with fine grain structure and preparation method of TC4 titanium alloy bar

    CN114457259A

  • Preparation method of Ti6Al4V titanium alloy large-size bar

    CN114888219A